SOLUSI CERDAS UNTUK KEHIDUPAN MODERN DENGAN LUMIO BY SMART - Fajrianti, Dinda Tasya; Ulum, Siti Raudhatul; Viratama, Ika Putra (Sindoro: Cendikia Pendidikan, 2024)
The aim of this research is to increase teacher understanding in applying Lumio by Smart in learning. And also helps students in more flexible learning. The method used is a quantitative method utilizing Lumio (digital learning platform). Lumio provides various features that can be used over and over again. interactive learning videos and various learning activities. Data was collected through trials using Lumio so that the learning material was not interesting and student involvement was passive. By using Lumio, teachers can present learning in a more interesting way. The use of Lumio stimulates students' active participation and facilitates class discussions, thereby increasing their understanding of the lesson material.